Domestic Amplifiers of External Shocks : Growth Accelerations and Reversals in Emerging Market and Developing Economies - Gruss, Bertrand; Nabar, Malhar; Poplawski Ribeiro, Marcos (Washington, D.C. : International Monetary Fund, 2019)
External conditions have been found to influence the tendency of emerging market and developing economies to experience episodes of growth accelerations and reversals. In this paper we study the role of domestic policies and other structural attributes in amplifying or mitigating the effect that shifts in external conditions have on growth patterns in emerging market and developing economies over the past five decades. We find that these economies can enhance the growth impulse from external conditions by strengthening their institutional frameworks and adopting a policy mix that protects trade integration; permits exchange rate flexibility; and ensures that vulnerabilities stemming from high current account deficits and external debt, as well as high public debt, are contained.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet